Compassion without Cognitivism - Charlie Kurth (Humana.Mente: Journal of Philosophical Studies, 2019)
Compassion is generally thought to be a morally valuable emotion both because it is concerned with the suffering of others and because it prompts us to take action to their behalf. But skeptics are unconvinced. Not only does a viable account of compassion’s evaluative content—its characteristic concern—appear elusive, but the emotional response itself seems deeply parochial: a concern we tend to feel toward the suffering of friends and loved ones, rather than for individuals who are outside of our circle of intimates. In response, I defend a sophisticated, non-cognitivist account of compassion and explain how it avoids the difficulties that undermine other proposals.